Aplikasi Pupuk Cair Plus Silika Dengan Pupuk Anorganik N,P,K Terhadap Pertumbuhan dan Hasil Tanaman Padi (Oryza Sativa L.) Pada Inceptisol Jatinangor - Solihin, Eso; Sandrawati, Apong; Kurniawan, Wawan; Maulana, Haris; Mutaqin, Zaenal (Jurnal Agro Wiralodra, 2021)
This experiment aims to determine the effect of various concentrations of liquid fertilizer plus silica combined with N, P, and K inorganic fertilizers on the growth and yield of rice plants (oryza zativa). The trial was conducted in July 2018 to November 2018 in the Ciparanje experimental garden of the Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang. The method used is Randomized Block Design (RBD) which consists of ten treatments with three replications; Treatment (A) Control, (B) standard NPK, (C) Plus Silica Liquid Fertilizer, (D) ¼ NPK + Silica Plus Liquid Fertilizer, (E) ½ NPK + Silica Plus Liquid Fertilizer, (F) ¾ NPK + Liquid Fertilizer Silica Plus, (G) NPK + Silica Plus Liquid Fertilizer, (H) ¾ NPK + ¼ Silica Plus Liquid Fertilizer, (I) ¾ NPK + ½ Silica Plus Liquid Fertilizer, (J) ¾ NPK + ¾ Silica Plus Liquid Fertilizer. The results showed that there was an effect of silica fertilizer on the growth and number of tillers after rice 8 MST. The treatment of F (¾ NPK + Liquid Fertilizer Plus Silica) gave the highest value to the yield of rice plants with the results of 53.31 gr of crop.